Numerical prediction of the elastoplastic response of FG tubes using nonlinear kinematic hardening rule with power-law function model under thermomechanical loadings. Issue 1 (29th November 2018) - Mehditabar, Aref; Rahimi, Gholam H.
Abstract : Purpose: This study aims to explain the characterization of cyclic behavior of a tube made of functionally graded material (FGM) under different combinations of internal pressure and cyclic through-thickness temperature gradients. Design/methodology/approach: The normality rule, nonlinear kinematic hardening Chaboche model and Von Mises yield criterion were used to model the constitutive behavior of an FG tube in the incremental form. The material properties and hardening parameters of the Chaboche model vary according to the power-law function in the radial direction. The backward Euler integration scheme combined with return mapping algorithm which relies on the solution of a nonlinear equation performs the numerical procedure. The algorithm is implemented within the user subroutine UMAT in ABAQUS/standard. Findings: The published works on FG components considering only the mechanical and physical properties as a function of spatial coordinate and nonlinear kinematic hardening parameters have not been considered to be changed continuously from one surface to another. Motivated by this, the present paper has deliberately been targeted to tackle this kind of problem to simulate the cyclic behavior of an FG tube as accurately as possible. In addition, to classify various behaviors the FG tube under cyclic thermomechanical loadings, Bree's interaction diagram as an essential tool in designing of the FG pressure vessels in many engineering sectors is presented. Originality/value: Provides a detailed description of the FG parameters of Chaboche kinematic hardening parameters in the adopted constitutive equations. In this paper, the significant effects of internal pressure values, kinematic hardening models and also FG inhomogeneity index related to the hardening rule parameters on plastic deformation of the FG tube are illustrated. Finally, the various cyclic behaviors of the FG tube under different combinations of thermomechanical loading are fully explored.